“You are not clean until you’re not on anything”: Perceptions of medication-assisted treatment in rural Appalachia - Richard, Emma L (Int J Drug Policy, 2020)
BACKGROUND: Medication-assisted treatment (MAT) is an evidence-based strategy to treat opioid use disorder (OUD). However, MAT-related stigma reduces MAT uptake, which is particularly low in rural areas. To date, perceptions and attitudes towards MAT in rural settings have not been described. OBJECTIVE: This qualitative study aims to characterize perceptions and attitudes towards MAT and the environmental factors contributing to these views in Appalachian Ohio. METHODS: From February to July 2018, semi-structured interviews were conducted with 34 stakeholders (12 healthcare professionals, 12 substance use treatment providers, 7 law enforcement agents and judicial officials, and 3 members of relevant organizations) in three rural counties in Appalachian Ohio. Interviews were transcribed, coded, and analyzed to characterize the risk environment and participants’ perceptions and attitudes towards MAT. RESULTS: Participants expressed or described pervasive MAT-related stigma in the region. Participants consistently described three elements of the environment affecting stigma: (1) a “conservative” culture in which abstinence is necessary to be in recovery successfully; (2) fear of medication diversion and abuse; (3) drug court policies that keep MAT out of the criminal justice system. CONCLUSION: MAT-related stigma will need to be addressed to tackle the opioid epidemic through evidence-based treatment effectively.